Technical Analysis Applications - Luca Cornelius (McGraw -Hill, 2004)
While investors are naturally curious about the documented successes of technical analysis, many find themselves stymied by the density of most books on the subject. Technical Analysis Applications is one of the first books to make the entire subject cohesive, practical, and understandable. It covers the use of technical analysis in a variety of markets—stocks, futures, bonds, and currencies—and situations, and provides in-depth details on trends and trend patterns, characteristics and uses of popular charts, and much more.